Symbols and Strategies: Acts of Métis Resistance - Using the List of Rights as a Framework for the Reclamation of Indigenous Child Welfare in British Columbia and Canada - Thomas, Daleen Adele (First Peoples Child & Family Review, 2010)
This article engages the reader in comparing the Métis List of Rights, originally authored by Louis Riel, with the current state of Indigenous child welfare in British Columbia and Canada. The relationship between children’s resiliency and cultural resiliency is explored. Using a critical lens, a framework defining the progression of social regulation is presented. This paper begins by setting out the framework with its accompanying nine aspects: profit, competition, self-interest, justice, rights, duties, love, compassion and devotion. The discussion acknowledges children as sacred which allows us to move beyond conservative and socialist ideals. Then there is a discussion on the aspects of the Métis List of Rights with comments respecting the symbolic and literal application of the aspects to reclaiming Indigenous child welfare. Finally the article ends with recommendations for holistic pathway for reform.